Linking the low‐density lipoprotein receptor‐binding segment enables the therapeutic 5‐YHEDA peptide to cross the blood‐brain barrier and scavenge excess iron and radicals in the brain of senescent mice. Issue 1 (1st January 2019) - Zou, Zhenyou; Shao, Shengxi; Zou, Ruyi; Qi, Jini; Chen, Liguan; Zhang, Hui; Shen, Qiqiong; Yang, Yue; Ma, Liman; Guo, Ruzeng; Li, Hongwen; Tian, Haibo; et al.
Abstract: Introduction: Iron accumulates in the brain during aging, which catalyzes radical formation, causing neuronal impairment, and is thus considered a pathogenic factor in Alzheimer's disease (AD). To scavenge excess iron‐catalyzed radicals and thereby protect the brain and decrease the incidence of AD, we synthesized a soluble pro‐iron 5‐YHEDA peptide. However, the blood‐brain barrier (BBB) blocks large drug molecules from entering the brain and thus strongly reduces their therapeutic effects. However, alternative receptor‐ or transporter‐mediated approaches are possible. Methods: A low‐density lipoprotein receptor (LDLR)‐binding segment of Apolipoprotein B‐100 was linked to the 5‐YHEDA peptide (bs‐5‐YHEDA) and intracardially injected into senescent (SN) mice that displayed symptoms of cognitive impairment similar to those of people with AD. Results: We successfully delivered 5‐YHEDA across the BBB into the brains of the SN mice via vascular epithelium LDLR‐mediated endocytosis. The data showed that excess brain iron and radical‐induced neuronal necrosis were reduced after the bs‐5‐YHEDA treatment, together with cognitive amelioration in the SN mouse, and that the senescence‐associated ferritin and transferrin increase, anemia and inflammation reversed without kidney or liver injury. Discussion: bs‐5‐YHEDA may be a mild and safe iron remover that can cross the BBB and enter the brain to relieve excessive iron‐ and radical‐induced cognitive disorders.